De l’expérience kinesthésique à la structuration prépositionnelle du schème-image du chemin - Aurélie Barnabé (Corela)
Cognitive linguistics posits that linguistic structures are tied to conceptual structures. Image schemas belong to these structures. Schemas are shaped by socio-physical experience, and accordingly they have a firm cultural and sensor-motor basis. The present study aims at accounting for the development of the PATH schema on the basis of its kinesthetic origin. The epistemic investigation of the mere concept of “image-schema” will make it easier to focus on the linguistic structure of the PATH schema and of its enacted experience. The most fundamental concept arising from this image-schema is the experience of space, which represents a guide as well as a constraint for the conceptualizer. It also marks the basis of multiple conceptualisations of the cognitive being. Moreover, in this study, we will try to assign a prepositional structure to the PATH schema on the basis of micro-analyses of examples extracted from a corpus-based analysis composed of 500 occurrences.